The immunogenicity of ReFacto AF (moroctocog alfa AF‐CC) in previously untreated patients with haemophilia A in the United Kingdom. Issue 6 (13th July 2018) - Mathias, M. C.; Collins, P. W.; Palmer, B. P.; Chalmers, E.; Alamelu, J.; Richards, M.; Will, A.; Hay, C. R. M.; ,
Abstract : Introduction: Factor VIII inhibitor development is currently the most serious complication of the treatment of haemophilia A. Differences in manufacturing and the molecular structure of brands of recombinant factor VIII have led to speculation that concentrates may differ in immunogenicity. This has led to a regulatory focus on the immunogenicity of factor VIII concentrates both before and after licensure. Aim: To investigate the immunogenicity of ReFacto AF post licensure in a real‐world setting in previously untreated patients (PUPs) treated exclusively with this product until at least 50 exposure days (EDs). Methods: The United Kingdom Haemophilia Centre Doctors' Organisation (UKHCDO) National Haemophilia Database (NHD) identified a consecutive cohort of patients with severe haemophilia A (<0.01 IU/L) whose first treatment was with ReFacto AF, monitored time to inhibitor development and described associated risk factors. Results: One hundred and three boys reached 50 EDs within the study period, of whom 35 developed an inhibitor ( P ( t  ≤ 50) = 0.33, [95% CI: 0.25‐0.43]), of which 15 ( P ( t  ≤ 50) = 0.16, [95% CI: 0.10‐0.25]) were high titre. Inhibitors arose after a median (interquartile range) 11 (7‐16) EDs. Inhibitors were significantly associated with high‐risk mutations and non‐significantly associated with non‐white ethnicity. Inhibitors were negatively associated with a family history of haemophilia A. High‐titre inhibitors were significantly associated with a family history of inhibitors. Conclusion: Inhibitor incidence in a single country population of ReFacto AF PUPs was similar to that previously described. Low‐ and high‐titre inhibitors were detected after a similar number of EDs, contrasting with previous data, probably reflecting standardized inhibitor monitoring within the United Kingdom.